الاتساق النصي في قصيدة الأطلال لابراهيم ناجي - هويدي, شافو, نور السادات حمزة (University of El-oued, 2022)
شهدت الدراسات اللغويّة كغيرها من العلوم تطورا مشهودا في نظرياتها ومناهجها ومنطلقاتها، فلم تعد جهود علماء اللغة منصبة على دراسة الجملة باعتبارها وحدة كبرى بل تعدتها إلى التآلف الجمليأو ما يسمى بالنص، فظهرت لسانيات النّص كعلم يعنى بدراسة النص من خلال تسليط مجموعة من المعايير اقترحعا دي بوجراند لنحكم من خلالها على نصيّة النص من عدمها، ومن أهمّها الاتساق النصي، فجاءت هذه الدراسة منطلقة من هذا المبدأ من خلال تحليل لساني لقصيدة الأطلال لإبراهيم ناجي للكشف عن مدى اتساقها وأهمّ مظاهره في القصيدة متمثلة في الاتساق النحوي: الإحالة والحذف والاستبدال والوصل، والاتساق المعجمي: التكرار والتضام، فتتبعنا في هذا البحث هذه الآليات آلية آلية في القصيدة، وأتبعنا كلّ وسيلة اتساقيّة جدولا يحوي جميع الحالات مع أنواعها في كلّ بيت ودائرة نسبية لجميع الأليات بأنواعها كلّ بنسبة وروده، حيث تبيّن لنا في الأخير أن الشاعر قد وظف آليات الاتساق النصي بنسب متفاوتة، كان أكثرها الإحالة فالوصل ثمّ التكرار والحذف والاستبدال والتضام، وهذا ما مكننا بأن نحكم بنصيّة القصيدة وأنّها كلّ متكامل وبناء متسق ومترابط وهو ما يفضي إلى وضوح قصدية الشاعر وتمام المعنى تجاه متلقي القصيدة. Linguistic studies, like other sciences, have witnessed a remarkable development in their theories, curricula and premises. The efforts of linguists are no longer focused on studying the sentence as a major unit, but rather transcend it to the syntax or the so-called text. Text linguistics emerged as a science concerned with the study of the text by shedding a set of criteria that they proposed. Bougrand, in order to judge the textuality of the text or not, the most important of which is the textual consistency. This study came out of this principle through a linguistic analysis of Ibrahim Naji’s poem Al-Atlal to reveal the extent of its consistency and the most important manifestations in the poem represented in grammatical consistency: referral, deletion, replacement, connection, and lexical consistency. : Repetition and consolidation, so we followed in this research these mechanisms as an automatic mechanism in the poem, and we followed each method of consistency in a table that contains all cases with their types in each house and a relative circle for all the mechanisms of all kinds, each according to the proportion of its occurrence. Varying, the most of which was referral, then linking, then repetition, deletion, replacement, and merging, and this is what enabled us to judge the text of the poem and that it is an integrated whole, a coherent and coherent construction, which leads to the Clarity of the poet's intentionality and completeness of meaning towards the recipient of the poem.
Keywords: :لسانيات النص، الاتساق النصي، آليات الاتساق النحوي، آليات الاتساق المعجمي، الأطلال، إبراهيم ناجي; Linguistics of the text, textual consistency, mechanisms of grammatical consistency, mechanisms of lexical consistency, Al-Atlal, Ibrahim Naji